Evaluation of Trace Elements in Patients with Senile Cataract - Abdul Sattar Khan, Shahida Hassan Memon, Shakeel Ahmed Sheikh, Ali Raza Memon, Gunesh Kumar, Muhammad Yaqoob Shahani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Senile cataract is a common cause of blindness among older people. The problem is common among adults of age 40 and older. There are various factors that cause senile cataracts among adults. These factors include protein and lipid variations, genetic role, and the existence of trace elements like magnesium, zinc and copper. Aim and objectives: To evaluate the level of zinc and relationship between copper, and magnesium in patients with senile cataract by comparing with healthy subjects. Material and Methods: This study has a key focus on examining the effect of trace elements on senile cataract patients. We conducted experiments when 100 people (50 patients and 50 non-patients). Absorption spectrometry was used to examine the blood samples of the people who took part in the research. Results: It was noted during the results that most of the patients developed senile cataracts after crossing the age of 50. It was also noted from the results that the concentration of copper and zinc was higher in the patients as compared to the non-patients, while the concentration of magnesium was lower in the patients as compared to the non-patients. Based on these results, it can be stated that an increase in the concentration of copper and zinc increases the chances of senile cataracts. The decline in the concentration of magnesium increases the chances of senile cataracts. Also, out of these patients, a majority of them were females. Therefore, there are chances of biased results in this study that can be improved in future studies with the number of patients and an equal number of males and females. Conclusion: The concentrations of copper and zinc were significantly higher in patients than in the non-patients, whereas the concentration of magnesium was lower in the patients than in the non-patients. Based on these findings, it may be concluded that an increase in copper and zinc concentrations increases the risk of senile cataracts. Keywords: zinc, copper, magnesium, senile cataract, healthy subjects.